Pentingnya Studi Multilingual untuk Menyongsong AFTA 2015 - Manurung, Rosida Tiurma (Zenit, 2014)
The significance of knowing ASEAN cultures, including multilingual languages, is an effort to accommodate the ever-growing needs to welcome AFTA 2015. From the multilingual study, it is known that the uniqueness, varieties, work ethics, and cultural richness of ASEAN countries can bestudied and used as refereces by local HRD to enhance the quality of life and become professional HRD to be employed in foreign companies or industries in Indonesia. Multilingual study can be an alternative to supply competent HRD in introducing ASEAN cultures. Multilingual study refers to the study of variuos languages. Multilingualism is a phenomenon that prevails in a community with several languages. The development of monolingualism to bilingualism and eventually to multilingualis caused by several factors. The developmnt of communication technology, globalization, and education has caused a shift in people’s need in languages and indirectly mixed up languages.Keywords: multilingual study, language interaction, AFTA 2015, professional HRD